Gadolinium Enhancement in Intracranial Atherosclerotic Plaque and Ischemic Stroke: A Systematic Review and Meta‐Analysis. Issue 8 (August 2016) - Gupta, Ajay; Baradaran, Hediyeh; Al‐Dasuqi, Khalid; Knight‐Greenfield, Ashley; Giambrone, Ashley E.; Delgado, Diana; Wright, Drew; Teng, Zhongzhao; Min, James K.; Navi, Babak B.; Iadecola, Costantino; Kamel, Hooman
Abstract : Background: Gadolinium enhancement on high‐resolution magnetic resonance imaging (MRI) has been proposed as a marker of inflammation and instability in intracranial atherosclerotic plaque. We performed a systematic review and meta‐analysis to summarize the association between intracranial atherosclerotic plaque enhancement and acute ischemic stroke. Methods and Results: We searched the medical literature to identify studies of patients undergoing intracranial vessel wall MRI for evaluation of intracranial atherosclerotic plaque. We recorded study data and assessed study quality, with disagreements in data extraction resolved by a third reader. A random‐effects odds ratio was used to assess whether, in any given patient, cerebral infarction was more likely in the vascular territory supplied by an artery with MRI‐detected plaque enhancement as compared to territory supplied by an artery without enhancement. We calculated between‐study heterogeneity using the Cochrane Q test and publication bias using the Begg‐Mazumdar test. Eight articles published between 2011 and 2015 met inclusion criteria. These studies provided information about plaque enhancement characteristics from 295 arteries in 330 patients. We found a significant positive relationship between MRI enhancement and cerebral infarction in the same vascular territory, with a random effects odds ratio of 10.8 (95% CI 4.1–28.1, P <0.001). No significant heterogeneity (Q=11.08, P =0.14) or publication bias ( P =0.80) was present. Conclusions: Intracranial plaque enhancement on high‐resolution vessel wall MRI is strongly associated with ischemic stroke. Evaluation for plaque enhancement on MRI may be a useful test to improve diagnostic yield in patients with ischemic strokes of undetermined etiology.